Machine Learning Algorithm Using Electronic Chart-Derived Data to Predict Delirium After Elderly Hip Fracture Surgeries: A Retrospective Case-Control Study - Zhao, Hong; You, Jiaming; Peng, Yuexing; Feng, Yi (Frontiers in Surgery, 2021)
Background: Elderly patients undergoing hip fracture repair surgery are under increased risk of delirium due to ageing, comorbidities and frailty. But current methods for identifying high risk of delirium among hospitalized patients have moderate accuracy and require extra questionnaires. Artificial intelligence makes it possible to establish machine learning models that predict incident delirium risk based on electronic health data. Methods: We conducted a retrospective case-control study on elderly patients (≥ 65 years of age) who received orthopedic repair with hip fracture under spinal or general anesthesia between June 1, 2018 and May 31, 2019. Anesthesia records and medical charts were reviewed to collect demographic, surgical, anesthetic features and frailty index to explore potential risk factors for postoperative delirium. Delirium was assessed by trained nurses using Confusion Assessment Method (CAM) every 12 hours during hospital stay. Four machine learning risk models were constructed to predict incidence of postoperative delirium: random forest, eXtreme Gradient Boosting (XGBoosting), support vector machine (SVM) and multilayer perception (MLP). K-fold cross-validation was deployed to accomplish internal validation and performance evaluation. Results: 245 patients were included and postoperative delirium affected 12.2% (30/245) of the patients. Multiple logistic regression revealed that dementia/history of stroke (OR 3.063, 95% CI (1.231, 7.624)), blood transfusion (OR 2.631, 95% CI (1.055, 6.559)) and preparation time (OR 1.476, 95% CI (1.170, 1.862)) were associated with postoperative delirium, achieving an area under receiver operating curve (AUC) of 0.779, 95%CI (0.703, 0.856). Accuracy of machine learning models for predicting the occurrence of postoperative delirium ranged from 83.67% to 87.75%. Machine learning methods detected 16 risk factors contributing to the development of delirium. Preparation time, frailty index, uses of vasopressors during the surgery, dementia/history of stroke, duration of surgery and anesthesia were the six most important risk factors of delirium. Conclusion: Electronic chart-derived machine learning models could generate hospital-specific delirium prediction models and calculate the contribution of risk factors to the occurrence of delirium. Further research is needed to evaluate the significance and applicability of electronic-chart derived machine learning models for detection risk of delirium in elderly patients undergoing hip fracture repair surgeries.